Oligosaccharide Chromatographic Techniques for Quantitation of Structural Process-Related Impurities in Heparin Resulting From 2-O Desulfation - Anger, Pascal; Martinez, Céline; Mourier, Pierre; Viskov, Christian (Frontiers in Medicine, 2018)
Heparin is a widely-used intravenous anticoagulant comprising a complex mixture of highly-sulfated linear polysaccharides of repeating sequences of uronic acids (either iduronic or glucuronic) 1->4 linked to D-glucosamine with specific sulfation patterns. Preparation of crude heparin from mammalian mucosa involves protease digestion with alcalase under basic conditions (pH ≥ 9) and high temperature (>50°C) and also oxidation. Under such conditions, side reactions including the ubiquitous 2-O desulfation occur on the heparin backbone yielding non-endogenous disaccharides within polysaccharide chains. Whatever the process used for its manufacture, some level of corresponding degradation impurities is therefore expected to be found in heparin and the derived Low Molecular Weight Heparins. These impurities should be monitored to control the quality of the final therapeutic product. Two anion exchange chromatography techniques were used to analyze heparin samples exhaustively or partially depolymerized with heparinases and determine the proportions of non-endogenous disaccharides generated by side reactions during the manufacturing process (epoxides and galacturonic moieties). We also present data from a case study of marketed heparin. Current heparin sodium monographs do not directly address process impurities related to modification of the structure of heparin. Although desulfation reduces the overall biological potency, we found that heparin with an average of one modified disaccharide per chain can still comply with the USP or Ph. Eur. heparin sodium monographs requirements. We have implemented disaccharide analysis to monitor the quality of this product on a risk basis.